2013
DOI: 10.1371/journal.pntd.0002062
|View full text |Cite
|
Sign up to set email alerts
|

The Household Costs of Visceral Leishmaniasis Care in South-eastern Nepal

Abstract: Background and objectivesVisceral leishmaniasis (VL) is an important public health problem in south-eastern Nepal affecting very poor rural communities. Since 2005, Nepal is involved in a regional initiative to eliminate VL. This study assessed the economic impact of VL on households and examined whether the intensified VL control efforts induced by the government resulted in a decrease in household costs.MethodsBetween August and September 2010, a household survey was conducted among 168 patients that had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 15 publications
1
59
0
Order By: Relevance
“…The effects of VL on the economy are evident because this disease mainly affects low-income populations, and the direct and indirect costs related to diagnosis and treatment are high [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of VL on the economy are evident because this disease mainly affects low-income populations, and the direct and indirect costs related to diagnosis and treatment are high [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent study in Nepal showed that indirect cost increased from 47% in 2006 9 to 53% in 2010. 11 This may be because most affected individuals live in remote villages that are far away from the free government health-care facilities, which are usually located in the cities and urban centers. Because leishmaniasis is primarily more common in rural areas and villages, many of the affected individuals patronize the more expensive and often inadequate private health-care facilities located in these villages.…”
Section: Socioeconomic Impact Of Leishmaniasismentioning
confidence: 99%
“…In another study, 51% of households exceeded catastrophic threshold of 10% of the annual household income. 11 It is interesting to note that without the provision of free drugs, the catastrophic index would have increased from 51-74%. 11 The implication of catastrophic payments may be seen as changes in treatment-seeking behavior from the formal to informal health sector.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that every rupee invested in VL control in Nepal at present (2010) will yield 71 rupees in future. (51). Yet investments are required, and strong commitments from political stakeholders as well as funding agencies are crucial to achieve the elimination goal.…”
Section: Is Vl Elimination Operationally Achievable?mentioning
confidence: 99%